Practical Syntheses of Triacylglycerol Regioisomers Containing Long‐chain Polyunsaturated Fatty Acids - Fraser, Benjamin H.; Perlmutter, Patrick; Wijesundera, Chakra (Journal of the American Oil Chemists' Society, 2006)
Abstract Docosahexaenoic acid (DHA, 22:6n‐3) is known to protect against a range of degenerative disease conditions and aid in the development of eye and brain function in infants. In dietary lipids DHA is found primarily in the triacylglycerol (TAG) form. However, the effects of the positional distribution of DHA in TAG on lipid functional properties such as bioactivity and oxidative stability are not clearly understood. Studies on this subject for the most part are limited by a lack of regioisomerically pure TAG model compounds containing DHA or similar long‐chain (LC)‐polyunsaturated fatty acids (PUFA). This paper reports on the development of a practical procedure, based on chemical and enzymatic reactions, for the syntheses of regioisomerically enriched, symmetrical and unsymmetrical TAG isomers containing two palmitic acid and one of linoleic acid, linolenic acid, or DHA. 1,3‐Selective acylation of glycerol with vinyl esters of fatty acids catalyzed by Candida antarctica lipase and direct coupling with fatty acids in the presence of the coupling agents 1‐(3‐dimethylaminopropyl)‐3‐ethylcarbodiimide hydrochloride and 4‐dimethylaminopyridine furnished 1,3‐dihexadecanoyl‐2‐docosahexaenoyl glycerol and its unsymmetrical isomer 1,2‐dihexadecanoyl‐3‐docosahexaenoyl glycerol in 99 and 60% yield, respectively. Critical to the success of the unsymmetrical TAG synthesis is the demonstration that PUFA‐containing glycerol acetonides can readily survive appropriately tailored acid‐catalyzed conditions. In this way, sufficient quantities of highly regioisomerically enriched PUFA‐containing unsymmetrical monoacylglycerols (MAG) and TAG have now become routinely accessible. The methods are amenable to scale‐up and could be adopted for regioenriched synthesis of a wide range of TAG.